The Impact of gender on ad processing a social identity perspective - Maldonado, Rachel; Tansuhaj, Patriya; Muehling, Darrel D. (Academy of Marketing Science, 2003)
Advertising is often as an efficient but sometimes in effective external influence on buyer behavior. Marketers are therefore seeking ways to make advertising more effective. This paper provides a theoritical framework explaining how ads can influence attitude and purchase intentions by activating an identity with one's gender group. A gender group identity is an example of a social identity in which one sees oneself as a member of his or her gender group. Such an identity could potentially be activated through exposure to ads that pair a brand with member of one's gender group. The identity activation is thought to bring about a gender group salience that results in behaviors consistent with group norms and in-group bias. The readiness or ease with which a gender group identity becomes salient may depend on how strongly a person with one's gender group. In this, paper, we propose that ads that activate identification with one's gender group will have a more favorable impact on future brand and ad judgments than do not activate this identity. A conceptual model is suggested for representing the proposed relationships between ads that activate a gender group identity, gender group identity salience and strength, and ad and brand judments. We draw from there areas of the literature to support our propositions and conceptual model: social identity theory, ad processing, and gender research.